The Potential Development of Agro-tourism of Patthawi Community, Chanthaburi Province - Tongla, Prempreeda; Burakachonkun, Nantapak (Suan Dusit Graduate School Academic Journal, 2022)
The purposes of this research were as follows: 1) to study the components of agro-tourism of Patthawi community,2) to assess the potential of agro-tourism, 3) to propose guidelines for developing the potential of agro-tourism of Chanthaburi province, and 4) to propose the travel route of Patthawi community, Chanthaburi province. The qualitative research was conducted in this research. The 30 key informants recruited by purposive sampling consisted of government agencies and local community members. The research instruments included structured interview form, Agritourism Standards Assessment Form and focus group discussion. The findings showed that 1. the components of agro-tourism of Patthawi community consisted of 5 components as follows; 1) Attraction: organic agrotourism was the tourism attraction of Patthawi community. 2) Accessibility, tourists can access to tourism destinations fast, safe and comfortably. 3) Accommodation, accommodation service was not available in the community. 4) Tourism activities; visiting organic garden, visiting the product processing in the community, tasting rare local durian species, buying souvenirs and 5) Facilities, Patthawi community had full facilities. 2. The result of potential assessment of Agro-tourism Management of Pattavee Community, Chanthaburi Province was indicated at a good level with an average of 66.45. 3. The total of 6 community-based tourism management plans were proposed including tourism management, marketing, activities, souvenirs, physical aspects and facilities. 4. The travel routes for tourism in Pattavee community during peak and off season of tourism offered diversity and uniqueness to impress tourists.